ASSESSMENT OF AMLODIPINE ANTIHYPERTENSIVE EFFECT HOMOGENEITY IN CONTROLLED TRIAL - V. M. Gorbunov; M. I. Smirnova; A. D. Deev (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To compare influence of amlodipine and spirapril on ambulatory blood pressure profile, including antihypertensive effect smoothness in patients with arterial hypertension (HT). Methods. 39 patients (aged 53,7±10,0 y.o.) with HT were included in the open, randomized, cross-over study, 30 patients completed study. The duration of every therapies was 4 weeks, initial control period and wash-out period between therapies lasted 1 week. The initial daily dose of amlodipine was 5 mg, standard dose of spirapril (6 mg/daily) was not changed during the trial. After 1-2 weeks of treatment amlodipine dose was increased up to 10 mg/daily as well as dihydrochlorothiazide was added, if necessary. Ambulatory blood pressure monitoring (ABPM) was performed initially and at the end of both therapies. Results. Both drugs demonstrated good antihypertensive effect according to ABPM data. Decrease of systolic/diastolic blood pressure was 11,2±1,8/7,6±1,2 mm Hg in amlodipine therapy and 10,0±1,8/7,1±1,2 in spirapril therapy (p<0,0001). The smoothness indexes (SI) were 0,65/0,45 and 0,55/0,45, respectively, differences between two therapies were not significant. However the individual analysis of the SI distribution (with SI=0,5 as a satisfactory criterion), showed that antihypertensive effect smoothness is better in amlodipine therapy than this in spirapril one. Conclusion. Amlodipine has prominent as well as smooth antihypertensive effect, that gives it advantages in the long-term antihypertensive therapy.